Flexible and Multifunctional Skin Patch for Clinical Decision Support in Psychiatric Assessment - Kim, Namyun; Lee, Soo Hyun; Lee, Yi Jae (JOHN WILEY & SONS INC, 2025)
The recent advances in flexible and wearable electronics, along with ubiquitous biosensing technologies have enabled the continuous monitoring of health conditions outside of medical facilities. Health-monitoring tools based on wearable sensors must be more user-friendly, informative, and cost-effective for daily applications owing to the increased prevalence of chronic diseases and mental illnesses. In this study, a flexible and multifunctional skin patch and a custom-designed application for wirelessly monitoring the wearer's physical and mental health conditions are proposed. The optimized design and soft-covering materials of the skin patch enable long-term attachment to the body without causing discomfort or irritation to the wearer. Onboard processing of the signals enables real-time monitoring and signal acquisition of multiple biomarkers, including the blood oxygen saturation level (SpO2), pulse rate (PR), pulse rate variability (PRV), perfusion index (PI), body movement, and temperature during daily activities. The photoplethysmography (PPG)-based biomarkers acquired from various body sites are compared and calibrated to verify its performance. Demonstrated pilot trial shows the potential application of the skin patch for clinical decision support in psychiatric assessments that can be implemented as an assistive mental illness monitoring system for psychiatrists and researchers.